Anionic cyclometallated Pt(ii) square-planar complexes: new sets of highly luminescent compounds. Issue 37 (14th September 2017) - Ricciardi, Loredana; La Deda, Massimo; Ionescu, Andreea; Godbert, Nicolas; Aiello, Iolinda; Ghedini, Mauro
Abstract : Novel anionic Pt(ii ) complexes were synthesized, displaying an outstanding enhancement of the emission efficiency in the solid state. Abstract : Two series of novel NBu4 + salts of anionic cyclometallated Pt(ii ) complexes were synthesized and fully characterized. These highly luminescent compounds (NBu4 [(C^N)Pt(O^N)] and NBu4 [(C^N)Pt(O^O)]) are incorporated as testing examples of cyclometallating ligands 2-phenylpyridine (PhPy), 2-(2, 4-difluorophenyl)-pyridine (F2 PhPy) and 2-thienylpyridine (ThPy), and a benzo[ h ]quinoline (Bzq) fragment. All complexes display a square-planar coordination sphere, wherein the "(C^N)Pt" fragment is completed either by an O^N orotate (Ort) or an O^O tetrabromocatecholate (Cat) ligand. The HOMO and LUMO levels of all complexes were estimated by cyclic voltammetry and a comprehensive electrochemical and photophysical study was performed. The new complexes are emissive in solution at 298 K and the NBu4 [(ThPy)Pt(Ort)] complex displays good photosensitizing properties ( Φ = 28% in deaerated solution vs. Φ = 1.4% in the presence of O2 ). Both series of NBu4 [(C^N)Pt(Ort)] and NBu4 [(C^N)Pt(Cat)] complexes are highly luminescent in the solid state (emission quantum yields from 10 to 85%). Remarkably, the square-planar Pt(ii ) anionic complexes showed an important increase in luminescence quantum yields on changing from the dilute solution to the solid state (the most significant from 0.13% to 85% for the NBu4 [(PhPy)Pt(Ort)] complex, an ideal candidate as an active species for LEECs).